Penolakan Omnibus Law Menurut Paradigma Sosiologi Hukum dan Teori Konflik - Nada I Asmani; Agus Machfud Fauzi (Law Department, Sharia and Law Faculty., 2021)
The Omnibus Law, which has been valid and has become a regulation in the constitution in Indonesia, has experienced many new things in the process and has not opened up the flow of democracy from the people. There were several articles that were changed, especially regarding employment which eventually got rejected in society. Workers as subjects who are bound by the Omnibus Law are also involved in demonstrations and expect a change to the law. In terms of legal sociology, social revolution, as the answer desired by modern society today, will never occur because it is hampered by social mobility through the decomposition of the new labor force and middle class. Articles that have the potential to become a legality tool for suppressing human rights and discriminating against workers against employees must be further guarded by academics so that practices of abuse of the rules in the Omnibus Law will not occur.